Impact of Hydrophobic Surfaces on Mass Transfer in Structured Packings - Pietro Giustacori; Sara Marchini; Elisabetta Brunazzi; Uwe Hampel; Markus Schubert (Chemical Engineering Transactions)
This study investigates a potential alternative to traditional film flow in structured packings operating at low liquid loads, aiming to improve mass transfer performance by increasing the gas-liquid interfacial area. The potential of small droplet flow, which theoretically offers a significantly higher interfacial area compared to film flow, was investigated. The water affinity of the structured packing surface was modified by applying self-assembled monolayer (SAM) coatings. Contact angles, droplet behavior and coalescence tendencies were investigated on smooth, corrugated and embossed metal sheets to identify the best combination of SAM system and coating process. The mass transfer performance of SAM-coated packings was compared to standard packings by stripping isobutyl acetate with air. These tests showed that the SAM coated packings tested had lower liquid holdup and therefore lower mass transfer efficiency compared to uncoated packings. However, the study provides a valuable methodology and framework for evaluating the performance of other structured packing surface treatments.